2018
DOI: 10.19177/rgsa.v7e32018129-149
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização Da Coleta Seletiva Em Mundo Novo/MS

Abstract: Diante do volume crescente de resíduos sólidos gerados e dos diversos impactos negativos decorrentes da disposição inadequada dos mesmos, torna-se necessária a adoção de estratégias para a gestão integrada, sendo a coleta seletiva e, posteriormente, a reciclagem prevista na Política Nacional de Resíduos Sólidos. No município de Mundo Novo/MS, a coleta seletiva é realizada por integrantes da Associação dos Recicladores Ambientais Mundonovenses (ARAM). Entretanto, não há informações sistematizadas sobre o materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Alencar (2012) showed that the majority of the pickers' income was between R$ 300.00 and R$ 700.00, and points out that the income depends on what they are able to collect, the climatic conditions and the population's awareness. Meireles and Moraes (2018) commented that, since January 2012, the Mundo Novo's Recyclers Association (ARAM) has a responsible for articulating the entity's actions. The collected material is sold to a company in the city of Amambai (MS), and the amount collected from the sale of the material is R$ 9,200.00, on average.…”
Section: Of the Questionnaires Applied To Recyclable Materials Collectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alencar (2012) showed that the majority of the pickers' income was between R$ 300.00 and R$ 700.00, and points out that the income depends on what they are able to collect, the climatic conditions and the population's awareness. Meireles and Moraes (2018) commented that, since January 2012, the Mundo Novo's Recyclers Association (ARAM) has a responsible for articulating the entity's actions. The collected material is sold to a company in the city of Amambai (MS), and the amount collected from the sale of the material is R$ 9,200.00, on average.…”
Section: Of the Questionnaires Applied To Recyclable Materials Collectorsmentioning
confidence: 99%
“…It is worth mentioning that, in this last study, 75% of the interviewees reported that the value obtained from the sale of the materials is insufficient to support the family. However, as a way to increase the income of waste pickers, the authors Meireles and Moraes (2018) comment that ARAM receives support from the City Hall together with Itaipu Binacional According to Ferreira (1986), the meaning of the word trash gives the impression that it is something worthless, unimportant and that must be thrown away. However, the collectors questioned conceptualized garbage as something discarded by society, but which can be reused, serving as a source of income and survival.…”
Section: Of the Questionnaires Applied To Recyclable Materials Collectorsmentioning
confidence: 99%
See 1 more Smart Citation